Immobilization of AIEgens into metal‐organic frameworks: Ligand design, emission behavior, and applications. Issue 11 (21st March 2017) - Gui, Bo; Yu, Na; Meng, Yi; Hu, Fang; Wang, Cheng
ABSTRACT: Aggregation‐induced emission (AIE), in which the luminophores are highly emissive in aggregate state, is one of the most unique photophysical phenomena and has shown interesting applications in many areas. The immobilization of AIE luminogens (AIEgens) into metal‐organic frameworks (MOFs), which are inorganic‐organic hybrid porous materials with tunable and predictable structures, has been investigated over the past few years. These well‐defined porous frameworks cannot only provide an ideal platform for studying the mechanism of AIE phenomenon in solid state, but also show potential applications from sensing to white light‐emitting diodes. In this highlight, we will summarize the recent progress of AIEgens‐based MOFs, including ligand design, emission behavior, and applications. © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 1809–1817 Abstract : Aggregation‐induced emission (AIE) is a valuable phenomenon and has shown interesting applications in many areas. Immobilizing AIE luminogens (AIEgnes) into the metal‐organic frameworks (MOFs) as ligands has attracted increasing attention in the past few years. This review summarizes the recent progress of AIEgens‐based MOFs, including ligand design, emission behavior, and applications.